SOCIAL JUSTICE IN URBAN DEVELOPMENT: A SOCIOLOGICAL STUDY OF FORCED EVICTIONS AND COMMUNITY RESISTANCE IN JAKARTA - Lindström, Maria; Nilsson, Johan; Olsson, Ingrid (Cognitionis Civitatis et Politicae, 2025)
The rapid urbanization of Jakarta has led to increasing cases of forced evictions as part of urban development projects, often resulting in significant social and economic displacement for marginalized communities. Despite legal frameworks aimed at protecting the rights of these residents, forced evictions remain a persistent issue, raising concerns about social justice and inequality in urban planning. This research aims to explore the sociological dimensions of forced evictions in Jakarta, focusing on the experiences of displaced communities and their forms of resistance. Using a mixed-methods approach, this study combines qualitative interviews with affected residents and key stakeholders, along with an analysis of official documents and reports from NGOs. The findings reveal that forced evictions are often justified by development agendas that prioritize economic growth over the rights of local residents, exacerbating social inequalities. Furthermore, community resistance takes diverse forms, including legal battles, protests, and informal negotiations with local authorities. This study concludes that urban development in Jakarta often neglects the principles of social justice, with significant implications for the future of inclusive urban planning. It calls for more equitable development policies that prioritize the rights of displaced communities and ensure their participation in the decision-making process.